The Pathways Between Socioeconomic Status and Adolescent Outcomes: A Systematic Review. Issue 1 (27th January 2017) - Devenish, Bethany; Hooley, Merrilyn; Mellor, David
Abstract: Socioeconomic status (SES) is a significant risk factor for negative adolescent development outcomes. Identifying the pathways between SES and these outcomes may inform interventions for adolescents from this demographic. We conducted a systematic literature review of eight databases for studies investigating pathways between SES and adolescent psychosocial outcomes. A total of 59 articles met inclusion criteria. Significant risk factors identified include economic stress, chaos in the home, and violence in the community. These risk factors appear to be mediated through parent depression, conflict between parents, parenting practices, and adolescent resilience. Interventions focusing on the identified risk factors are recommended.